INSTITUTIONAL AND STUDENT FACTORS AS PREDICTORS OF LEARNING OUTCOMES IN REPRODUCTIVE HEALTH PROGRAMME AMONG TRAINEE MIDWIVES IN SOUTH-WESTERN NIGERIA (2020)
Reproductive health is one of the core programmes in midwifery education necessary for the competency development of the trainee midwife. Records have shown that trainee midwives' performance in Reproductive Health Programme (RHP) is on the decline in schools of midwifery across southwestern Nigeria. This has become worrisome and a major concern to nursing professionals and practitioners. Previous studies focused largely on curriculum development, availability of resource materials and tutor–related factors with less emphasis on institutional and student factors. This study, therefore, was designed to examine the institutional factors (Curriculum Content Knowledge-CCK, Continuous Professional Development-CPD and Learning Environment-LE) and student factors (Academic Support Seeking-ASS, Academic Self-efficacy-AS and Self-regulated Learning-SrL) as predictors of learning outcomes (knowledge, attitude to and skills) in RHP among trainee midwives in southwestern Nigeria. Bandura's Social Learning Theory provided the framework, while the survey design was adopted. The purposive sampling technique was used to select seven accredited Post-basic Schools of Midwifery (PbSM) in the South-west (Eleyele, Ogbomoso, Ado-Ekiti, Ilesa, Osogbo, Yaba and Idi-araba). The 30 nurse tutors and 228 final year trainee midwives were enumerated. Teachers (r=0.92) and Students (r=0.86) questionnaires were used. Knowledge of Reproductive Health (r=0.70), Skills Acquisition of Reproductive Health (r=0.70) and Attitude towards Reproductive Health (r=0.86)Tests were used. Focus group discussions were held with some trainee midwives in each PbSM. Quantitative data were analysed using Multiple regression at 0.05 level of significance while qualitative data were content analysed. The students' age was 27.74 ± 5.07 years; 73.3% had diploma certificate in nursing education, while 26.7% had first and higher degrees. The nurse tutors adopted teacher-centered teaching methods: practical demonstration (96.7%) and lecturing (90.0%), while modern teaching approaches were rarely used: seminar presentation (23.0%), simulation/Internet use (20.0%) and tutorial (22.0%). There were significant joint predictions of institutional factors on attitude (F(3;224)=17.02; Adj. R2=0.18); knowledge (F(3;224)=15.23; Adj. R2=0.16) and skills (F(3;224)=12.57; Adj. R2=0.13); accounting for 18.0%, 16.0% and13.0% of variance of reproductive health. There was a significant joint prediction of student factors on knowledge (F(3;224)=71.03; Adj. R2=0.48); skills (F(3;224)=55.83; Adj. R2=0.42) and attitude (F(3;224)=9.02; Adj. R2=0.10); accounting for 48.0%, 42.0% and 10.0% of variance of reproductive health. The CCK (β=0.39, β=0.34, β=0.37); CPD (β=0.04, β=-0.04, β=0.02) and LE (β=0.08, β=0.26, β=0.06) had relative contributions to knowledge, attitude to and skills of reproductive health, respectively. The ASS (β=0.04, β=0.13, β=0.10); AS (β=0.48, β=0.34, β=0.36) and SrL (β=0.51, β=0.15, β=0.50) had relative contributions to knowledge, attitude to and skills of reproductive health, respectively. The learning environment lacked modern facilities for training. The trained nurse tutors were inadequate, while there were insufficient instructional materials and poor environment for teaching and learning. Curriculum content knowledge, continuous professional development, learning environment, academic support seeking, academic self-efficacy and self-regulated learning determined the knowledge of, attitude to and skills of reproductive health among trainee midwives in south-western, Nigeria. Therefore, there is need to give attention to modern teaching approaches, conducive environment and adequate instructional materials by the heads of schools of midwifery.